Comprehensive Identification and Expression Profiling of Circular RNAs During Nodule Development in Phaseolus vulgaris - Wu, Zhihua; Huang, Wen; Qin, Erdai; Liu, Shuo; Liu, Huan; Grennan, Aleel K.; Liu, Hong; Qin, Rui (Frontiers in Plant Science, 2020)
Symbiotic nitrogen fixation by legume nodules provides an abundant nitrogen source for plants, and understanding this process is key for developing green agriculture. Circular RNA (circRNA), a type of endogenous RNA produced by reverse splicing of mRNA precursors, plays important regulatory roles in plants at the transcriptional and post-transcriptional levels. However, the relationship between circRNAs and legume–rhizobium is unknown. Here, we performed comprehensive identification and expression profiling of circRNAs during nodulation in common bean (Phaseolus vulgaris) compared to uninoculated roots of corresponding ages by constructing circRNA-seq and mRNA-seq libraries. We identified 8,842 high-confident circRNAs, 3,448 of which were specifically produced during symbiosis, with the highest number at the nitrogen-fixing stage. Significantly, more circRNAs were derived from exons than from intergenic regions or introns in all samples. The lengths and GC contents of the circRNAs were similar in roots and nodules. However, circRNAs showed specific spatiotemporal expression patterns during nodule and root development. GO and other functional annotation of parental genes of differentially expressed circRNAs indicated their potential involvement in different biological processes. The expression of major circRNAs during symbiosis is independent of parental genes’ expression to a certain degree, while expression of the remaining minor circRNAs showed positive correlation to parental genes. Functional annotation of the targeted mRNAs in the circRNA–miRNA–mRNA network showed that circRNAs may be involved in transmembrane transport and positive regulation of kinase activity during nodulation and nitrogen fixation as miRNA sponges. Our comprehensive analysis of the expression profile of circRNAs and their potential functions suggests that circRNAs may function as new post-transcriptional regulators in legume–rhizobium symbiosis.